Investigating particle acceleration in Protostellar Jets: The triple radio continuum source in serpens - Rodríguez Kamenetzky, Adriana Raquel (2016)
While most protostellar jets present free-free emission at radio wavelengths, synchrotron emission has also been proposed to be present in a handful of these objects. The presence of nonthermal emission has been inferred by negative spectral indices at centimeter wavelengths. In one case (the HH 80-81 jet arising from a massive protostar), its synchrotron nature was confirmed by the detection of linearly polarized radio emission. One of the main consequences of these results is that synchrotron emission implies the presence of relativistic particles among the nonrelativistic material of these jets. Therefore, an acceleration mechanism should be taking place. The most probable scenario is that particles are accelerated when the jets strongly impact against the dense envelope surrounding the protostar. Here we present an analysis of radio observations obtained with the Very Large Array of the triple radio source in the Serpens star-forming region. This object is known to be a radio jet arising from an intermediate-mass protostar. It is also one of the first protostellar jets where the presence of nonthermal emission was proposed. We analyze the dynamics of the jet and the nature of the emission and discuss these issues in the context of the physical parameters of the jet and the particle acceleration phenomenon.